Pengaruh Pelatihan, Disiplin Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dinas Kesehatan Kota Kediri - Purwandari, Yeni; Askafi, Eka; Daroini, Ahsin (Universitas Islam Kadiri, 2023)
Every government and private institution with the development of the digitalization era, strives to be more able to empower its resources optimally. Each field is required to be able to adjust well and perform reliably. The success of an organization in achieving organizational goals is determined by the performance of employees. The formulation of the problem in this study is how effect of training on the performance of Kediri City Health Office employees, how discipline affects the performance of Kediri City Health Office employees, how the work environment affects the performance of Kediri City Health Office employees and how the influence of training, discipline, and work environment of Kediri City Health Office employees. The purpose of this study is to analyze the effect of each training variable (X1), discipline (X2), work environment (X3) on employee performance (Y) and how the variables training (X1), discipline (X2), work environment (X3) on employee performance (Y). The sampling method uses purposive random sampling, with a total population of 121 employees, so that the sample used is 100 employees. For data collection includes observation, questionnaire distribution and literature study. The analysis methods used are validity tests, reliability tests, multiple linear analysis and hypothesis tests. Based on the results of regression calculation Y = 7.670 + 0.082 X1 + 0.565 X2 + 0.572 X3 + e it can be known between the variables of training (X1) of 0.029 against employee performance (Y), discipline (X2) of 0.00 to employee performance (Y), work environment (X3) of 0.00. to employee performance (Y). Test results The t-test (correlational significance) of the training variable yielded a significance value of 0.643. This sig value < 0.05 then it can be said that H0 is rejected and Ha is accepted, The discipline variable produces a significance value of 0.000 This sig value < 0.05 then it can be said that H0 is rejected and Ha is accepted and the work environment variable produces a significance value of 0.000. This sig value < 0.05, it can be said that H0 is rejected and Ha is accepted, which means that there is an influence between training, discipline, work environment on employee performance. The output data shows an R-Square value of 0.792, This means that the variables of training, discipline, work environment affect employee performance 79.2%, the remaining 20.8% are influenced by other variables.